A mechanical evaluation of polyvinyl alcohol hydrogels for temporomandibular joint disc replacement - Kuiper, Jason P.; Puttlitz, Christian M.; Rawlinson, Jennifer E.; Dobbs, Ryan; Labus, Kevin M. (Frontiers in Physics, 2022)
The temporomandibular joint (TMJ) is a bilateral ginglymoarthroidal joint containing a fibrocartilaginous disc which distributes compressive stress and reduces friction on the articulating surfaces of the joint. Initially, conservative treatments can address disorders of the TMJ, but surgical procedures such as discectomy may be employed if dysfunction persists. Unfortunately, discectomy increases friction and alters the mechanical behavior of the TMJ when the disc is not replaced. An ideal replacement for the TMJ disc would restore healthy function of the joint and prevent further degeneration. Rigorous evaluation of materials is necessary to ensure the safety and efficacy of novel implants. Poly(vinyl) alcohol (PVA) hydrogels have been suggested as a good candidate for artificial cartilage replacement in other applications and are promising for replacing the TMJ disc due to their biocompatibility, low friction, and biomimetic levels of hydration. The objective of this study was to mechanically characterize hydrogel formulations of 15%, 20%, and 25% PVA and to compare them with the ovine TMJ disc to investigate the appropriateness of PVA hydrogels for TMJ disc replacement in a translational model. Experimental evaluations were conducted in indentation, unconfined compression, friction, and uniaxial tension. There were no statistically significant differences in the coefficient of friction between the PVA hydrogels and ovine TMJ disc. No statistically significant differences were found between at least one PVA hydrogel group and the TMJ disc for the indentation properties or the unconfined compression properties at low stretch magnitudes. The 20% PVA and 25% PVA hydrogels exhibited significantly higher toughness and failure stretch as compared to the ovine TMJ disc, and they were not statistically different in ultimate tensile strength from the TMJ disc in the mediolateral direction. However, the ovine TMJ disc tensile elastic moduli were 630 times larger in the anteroposterior direction and 53 times larger in the mediolateral direction than the stiffest PVA hydrogel. Ultimately, the 25% PVA hydrogel was the best candidate for TMJ disc replacement, demonstrating the most similarity to the ovine TMJ disc compressive properties; however, tensile reinforcement of the hydrogels would be necessary to approach the tensile modulus of the native TMJ disc.